A CRT-Informed Model to Enhance Experiences and Outcomes of Racially Minoritized Students. Issue 3 (27th May 2021) - Powell, Candice; Demetriou, Cynthia; Morton, Terrell R.; Ellis, James M.
Abstract : Racial inequities in retention and graduation rates are a top concern in higher education, yet scholars and practitioners rarely look to racism to explain these disparities. Critical Race Theory (CRT) is a vehicle to reveal and challenge power and oppression dynamics between racialized groups. This article proposes a practical model for student affairs professionals to leverage CRT concepts to address racial inequities in student outcomes and experiences.